Impact of Parental Substance Abuse on Children Later in Life - Brandewie, Madeline; Warren, Brittany; Kuebler, Anastasia; Lee, HeeSoon (Journal of Student Research, 2018)
Parental substance abuse in the home may negatively affect the health of their children. The purpose of this study is to better understand whether the impact of parental substance abuse on children persist into their adult lives. This study is a cross-sectional, exploratory study with quantitative methodology. Data was collected by SurveyMonkey, a web-based online survey tool. A total of 243 participants responded for the survey and the data was analyzed with the SPSS statistical software. Multivariate analysis (ANOVA) showed that regardless of age of children, there are significant main effects of mental and/or physical health issues in later life of children who experienced parental substance abuse. In addition, the young adult (18-30) group is more likely to have mental health issues than the middle-aged and older adult groups. The research findings indicate that those who have experienced family substance abuse are considerably likely to have mental health issues regardless of age. Key words: parental substance abuse, children, mental health, foster care